Investigating the Correlation Between STEAM-Based PjBL Supported by Augmented Reality and the Enhancement of 21st-Century Skills in Senior High School Students - Rahmawati, Dewi; Turista, Dora Dayu Rahma; Akhmad, Akhmad; Nasution, Ruqoyyah (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
This research investigates the correlation between STEAM-based Project-Based Learning (PJBL) enhanced by Augmented Reality and the development of 21st-century skills among students. The study employs a quantitative descriptive approach, utilizing a one-shot case study design. The sample was obtained through a cluster random sampling method. Data were analyzed using percentage analysis techniques and Kendall's tau-b test at a 5% significance level. The results from Kendall's tau-b test demonstrated a significant correlation between STEAM-based PJBL supported by Augmented Reality and enhancing students' 21st-century skills, with a correlation coefficient of 0.798 and a significance level of 0.000. Furthermore, observational data indicated that the average achievement of 21st-century skills was 77%, which is considered good. The study concludes that STEAM-based PJBL supported by Augmented Reality is significantly linked to improving students' 21st-century skills and effectively fosters these skills. These findings imply that integrating STEAM-based PJBL with Augmented Reality technology such as Assemblr Edu can be an effective strategy for educators to enhance 21st-century skills in secondary education settings.